Factor Influncing the Demand of Life Insurance Policy - Sapkota Manju (HM Journals, 2024)
This paper aims to investigate factors influencing life insurance purchase and what factors significantly affect customers towards the purchase of life insurance policies in Rupandehi district. Primary data have been collected through structured questionnaire out of 350 life insurance policyholder’s resident of Rupandehi district of Nepal. Sample was selected by Convenience sampling method. The paper has used regression models to analyze the relationship between dependent and independent variable. The result of the study reveals that level of education, age factor and people attitude and awareness has significantly associate with life insurance demand whereas income, family size, gender and health status has no significantly associate with life insurance demand.